Curcumin attenuates cognitive impairment by enhancing autophagy in chemotherapy - Li-Tao Yi; Shu-Qi Dong; Shuang-Shuang Wang; Min Chen; Cheng-Fu Li; Di Geng; Ji-Xiao Zhu; Qing Liu; Jie Cheng (Neurobiology of Disease, 2020)
Cisplatin, a commonly used chemotherapy drug, can increase the survival rate of cancer patients. However, it often causes various side effects, including neuronal deficit-induced cognitive impairment. Considering that curcumin is effective in neuronal protection, the action of curcumin on cognitive improvement was evaluated in cisplatin-treated C57BL/6 mice in the present study. Our results first showed that curcumin restored impaired cognitive behaviors. Consistent with this, neurogenesis and synaptogenesis were improved by curcumin. In addition, cisplatin-induced dysfunction of apoptosis-related proteins was partly reversed by curcumin. Moreover, cisplatin-induced autophagy was enhanced by curcumin. Our results also indicated that cisplatin induced autophagy through the endoplasmic reticulum (ER) stress-mediated ATF4-Akt-mTOR signaling pathway. Curcumin activated AMPK-JNK signaling, which mediated both mTOR inhibition and Bcl-2 upregulation and in turn enhanced autophagy and suppressed apoptosis, respectively. In contrast, pretreatment with the autophagy inhibitor 3-methyladenine (3-MA) completely abolished the effects of curcumin on cognitive improvement and improved neurogenesis, synaptogenesis and autophagy. Our results show that cognitive improvement induced by curcumin during chemotherapy is mediated by the enhancement of hippocampal autophagy.